Penerapan Kaidah Fiqh Al-Hajatu Tanzilu Manzilata Al-Dharurah dalam Kompleksitas Perubahan Kehidupan - Fahmi , Mutiara; Sufyan, Muhammad Suhaili (Program Pascasarjana IAIN Langsa, 2024)
Al-hajatu tanzzilu manzilata al-dharurah (the need to occupy an emergency position) is a fiqh rule that is often misunderstood in its use in an effort to justify changes to a law. The reason for using this method is often based on an urgent need that seems to be the same as or at least approaching an emergency. On the basis of an emergency, a law or legal procedure can be